Studi Pengukuran Partial Discharge Pada Bahan Resin Epoksi - Syakur, Abdul; AP, Winarko; Berahim, Hamzah; Sarjiya, Sarjiya; Rochmadi, Rochmadi (Departemen Teknik Elektro, Universitas Diponegoro, 2008)
Polimer materials now have been broadly used for high voltage isolation device. After long operation the polimer isolation can have degradation or decreasing in isolation quality until it became improper isolation. One main caused about this degradation is the deformity for instance the pointed conductor between the conductor to isolation interface that could make the partial discharge. Therefore is so important to have the information about the partial discharge characteristics of isolation material at operational condition. In this paper the research about the influences of voltage and application time of voltage to partial discharge characteristics was explained . This research used the epoxy resin for isolation and needle-plane electrode measurement method with 50 Hz ac voltage to investigate the partial discharge parameters such as the number of positive and negative charge and the maximum charge of positive and negative.Keywords: partial discharge, resin epoksi, elektroda jarum-bidang.